Analyzing the Spatial and Temporal Dynamics of Rainfall and Drought in The Vall River Basin, South Africa - Bodunrin, I. R.; Onyari, E. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Climate change continues to have devastating effects worldwide, particularly through drought, impacting billions of people. A recent study focused on the Vaal area in South Africa, a semi-arid region reliant on the Vaal River, a vital water resource. Researchers utilized the Standardized Precipitation Index (SPI) and Standardized Precipitation and Evapotranspiration Index (SPEI) to assess rainfall variability, evapotranspiration, drought, and trends over four decades. The results show some characteristics of Rainfall Patterns; such as Peak precipitation occurs during the January to March summer months while Drought Years: 2016 was identified as a hydrologically driest year for the Vaal River based on SPI and SPEI analysis at 12- and 24-month scales. Similarly, Agricultural Drought: Years like 1983, 1999, 2016, and 2019 exhibited agricultural drought, particularly evident in SPEI/SPI -3 and SPEI/SPI -6, crucial for local irrigation and agricultural production. Furthermore, for Temporal Consistency: SPI and SPEI demonstrated increasing temporal consistency with longer timescales until 2019, except for SPEI/SPI-1 and SPEI/SPI-48, which did not accurately represent drought in the Vaal River basin. Interestingly, the study highlights the escalating impact of climate change-induced drought in the Vaal area and underscores the importance of SPEI in assessing drought severity. Therefore, as climate conditions worsen globally, such analyses are vital for informed decision-making and effective water resource management.